2013
DOI: 10.1007/s10529-013-1375-3
|View full text |Cite
|
Sign up to set email alerts
|

Silencing the glycerol-3-phosphate dehydrogenase gene in Saccharomyces cerevisiae results in more ethanol being produced and less glycerol

Abstract: Transcription of the gene coding for glycerol-3-phosphate dehydrogenase (GPD1) was repressed in an industrial strain of Saccharomyces cerevisiae using a silencing vector. A fusion fragment containing GPD1 and Kan MX genes was generated by overlap extension PCR, then, the vector, pYES2.0 GPD1/Kan MX, was constructed by inserting the fusion fragment into the S. cerevisiae plasmid, pYES2.0. pYES2.0 GPD1/Kan MX, was linearized by KpnI, transformed into S. cerevisiae using the PEG/LiAc/ssDNA method, and integrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…7c). GPD1 is a key enzyme in glycerol biosynthesis 50 and He et al 49 also found the similar results, in which the strainS. cerevisiae DRY01 with silencing GPD1 dramatically decreased the glycerol accumulation.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…7c). GPD1 is a key enzyme in glycerol biosynthesis 50 and He et al 49 also found the similar results, in which the strainS. cerevisiae DRY01 with silencing GPD1 dramatically decreased the glycerol accumulation.…”
Section: Resultsmentioning
confidence: 56%
“…Previous research indicated that the glycerol biosynthetic pathway plays an important role in maintaining the intracellular NADH and NAD + level. 49 So obviously, the intracellular NADH level and NADH/NAD + ratio in strain X33-38 increased by 11.6% and 28.6% as compared with strain X33-37, respectively (Table 3). Meanwhile, strain X33-38 had certain improvement in both the intracellular NADPH level and the ATP level (Table 3).…”
Section: Resultsmentioning
confidence: 96%
“…The activity of GAPDH was determined using the method reported by He et al (2014). Substrate solution (100 µL) containing triethanolamine buffer (pH 7.9), 0.5 % bovine serum albumin, 0.2 mmol L − 1 NADH and 1 mmol L −1 dihydroxyacetone phosphate was added to a 96-well plate and incubated at 37 °C for 5 min, after which 100 µL cell-free extract was added and the plate was agitated for 5 min.…”
Section: Enzymatic Assaysmentioning
confidence: 99%
“…The precursor dihydroxyacetone phosphate (DHAP), an intermediate of glycolysis, is converted in a two-step reaction cascade to glycerol in the cytosol of Saccharomyces cerevisiae (He et al 2014). The first reaction, the conversion of DHAP to glycerol-3-phosphate (G3P), is catalyzed by NADH-dependent glycerol-3-phosphate dehydrogenase (Gpd p, reaction 1).…”
Section: Metabolic Pathwaymentioning
confidence: 99%
“…This pathway is of special interest to the bioethanol production industry (He et al 2014), because high rates of glycerol formation decrease the practical ethanol yields in current fermentation processes (Hubmann et al 2011). Since data on the glycerol biosynthetic pathway are widely available, we selected this pathway as a model for verifying our proposed approach.…”
Section: Introductionmentioning
confidence: 99%